A Fixed Point Theorem for Semi Compatible Maps in Fuzzy Metric Space - Jha, Kanhaiya (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The aim of the present paper is to establish a common fixed point theorem for semi-compatible pair of self maps in a fuzzy metric space which generalizes and improves various well-known comparable results.